Cytoplasmic redistribution and cleavage of AUF1 during coxsackievirus infection enhance the stability of its viral genome. Issue 7 (9th April 2013) - Wong, Jerry; Si, Xiaoning; Angeles, Arkhjamil; Zhang, Jingchun; Shi, Junyan; Fung, Gabriel; Jagdeo, Julienne; Wang, Tianying; Zhong, Zhaohua; Jan, Eric; Luo, Honglin
Abstract : Coxsackievirus B3 (CVB3) is a causative agent of viral myocarditis, hepatitis, pancreatitis, and meningitis in humans. The adenosine‐uridine (AU)‐rich element RNA binding factor 1 (AUF1) is an integral component in the regulation of gene expression. AUF1 destabilizes mRNAs and targets them for degradation by binding to AU‐rich elements in the 3′ untranslated region (UTR) of mRNAs. The 3′‐UTR of the CVB3 genome contains canonical AU‐rich sequences, raising the possibility that CVB3 RNA may also be subjected to AUF1‐mediated degradation. Here, we reported that CVB3 infection led to cytoplasmic redistribution and cleavage of AUF1. These events are independent of CVB3‐induced caspase activation but require viral protein production. Overexpression of viral protease 2A reproduced CVB3‐induced cytoplasmic redistribution of AUF1, while in vitro cleavage assay revealed that viral protease 3C contributed to AUF1 cleavage. Furthermore, we showed that knockdown of AUF1 facilitated viral RNA, protein, and progeny production, suggesting an antiviral property for AUF1 against CVB3 infection. Finally, an immunoprecipitation study demonstrated the physical interaction between AUF1 and the 3′‐UTR of CVB3, potentially targeting CVB3 genome toward degradation. Together, our results suggest that cleavage of AUF1 may be a strategy employed by CVB3 to enhance the stability of its viral genome.—Wong, J., Si, X., Angeles, A., Zhang, J., Shi, J., Fung, G., Jagdeo, J., Wang, T., Zhong, Z., Jan, E., Luo, H. Cytoplasmic redistribution and cleavage of AUF1 during coxsackievirus infection enhance the stability of its viral genome. FASEB J. 27, 2777‐2787 (2013). www.fasebj.org